Assessment of multi-hazards affecting service life of existing reinforced concrete (RC) bridges of Barak valley region, Assam, India. Issue 4 (1st October 2020) - Das, Joydeep; Sil, Arjun
ABSTRACT: The probabilistic approach for estimating deterioration of existing RC bridges due to multiple hazards becomes an important subject for the bridge management system. In the present study, a multi-hazard approach as well as investigation proposed to assess how service life of the bridges affected due to the amalgamation of the physical deterioration (aging) along with earthquake hazards. In this approach, the Weibull distribution is found suitable and employed for determining deterioration in terms of hazard function ha (t) of the bridges due to aging. Conversely, the northeast (NE) region of India is highly tectonically active and prone to earthquakes of higher magnitude (Mw>8). Considering the high seismicity in the study region, respective active faults and their corresponding maximum PGA values are taken into account to evaluate the earthquake hazard of the region in a site specific manner. By applying this proposed approach, significant site specific in-depth ideas and facts about their service life span could be evaluated considering the condition of existing bridges for satisfactory performance that would be helpful in taking rational decisions for the bridge management system (BMS) in terms of safety, rehabilitation, repair and inspection strategies of the bridges available in the study region for sustainable growth.